Análisis de la localización de los procesos y formas predominantes de la linea litoral de Chile: observación preliminar - Araya Vergara, José F. (Investigaciones Geográficas: Una mirada desde el sur, 1982)
A map - "Chile -shorelines: predominant landforms and processes" - was surveyed in order to analyze the location of shoreline phenomena and their degree of equilibrium (state). At the same time, the lenght of different groups of shoreline was measured. This preliminary inquiry points out some sites of scientific interest. Among rocky shorelines, mega-cliffs in Northern Chile, some soft cliffs in Central Southern Chile or some special sectors in lobate bays are emphasized. Respecting sandy-depositional shorelines, an unique rounded foreland is being prograded at present day and supports broad active systems. Other dune systems in Central Chile are detached too. Some fluvial outlets appear to be critical concerning their morphogenetic classification. Transitional areas of wave and wind environment allow the finding of the longshdre drift components. The lack of sufficien data causes criticism in front of quantitative results. But some supports may be founded as hypothesis. The Chilean shoreline is about 34.500 km long. More than 90% is cliffy and rocky and about 90% is stable. Rocky shorelines, because their longer length, show maior degree of uncertainty. Then, i t is not yet possible to set up a morphogenetic budget. Possibly 90% o more of the shoreline is in dynamic equilibrium and 6 %, in metastable equilibrium. Seven probable regional shoreline systems are proposed on the basis of predominant morphological elements and "inputs". On the other hand, five morphoclimatic zones are proposed on the basis of the groups of fluvial outlets. Central Chile is considered to have the optimum morphoclimatic condition for important sandy beachs and dunes systems.